Direct Conversion of Alcohols into Alkenes by Dehydrogenative Coupling with Hydrazine/Hydrazone Catalyzed by Manganese. (19th August 2018) - Das, Uttam Kumar; Chakraborty, Subrata; Diskin‐Posner, Yael; Milstein, David
Abstract: We have developed unprecedented methods for the direct transformation of primary alcohols to alkenes in the presence of hydrazine, and for the synthesis of mixed alkenes by the reaction of alcohols with hydrazones. The reactions are catalyzed by a manganese pincer complex and proceed in absence of added base or hydrogen acceptors, liberating dihydrogen, dinitrogen, and water as the only byproducts. The proposed mechanism, based on preparation of proposed intermediates and control experiments, suggests that the transformation occurs through metal–ligand cooperative N−H activation of a hydrazone intermediate.